PEMBUATAN KARBON AKTIF DARI CANGKANG BUAH KARET (Hevea brasilliensis) DENGAN AKTIVATOR H3PO4 DAN APLIKASINYA SEBAGAI PENJERAP Cr(VI) - Muhammad Zulfadhli; Iriany (Jurnal Teknik Kimia USU, 2017)
Activated carbon from lignocellulosic materials are renewable, abundant, and inexpesive. Rubber shell activated carbon that activated chemicaly has abilty to adsorp heavy metal. The purpose of this research is to study the effect of phosphoric acid concentration toward characteristics of rubber shell activated carbon, and its ability to adsorp Cr(VI). The materials used in this research are rubber shell, aquadest, and Cr(VI) solution. This research was started by impregnating rubber shell with phosphoric acid at 20%, 40% and 60% for 1 hour and then sample was carbonizated in furnace at 500oC for 1 hour. After that, activated carbon was applied to adsorp Cr(VI). The characteristic of surface area of rubber shell activated carbon are measured by BET method. Furthermore, the residual concentration of Cr(VI) was measured with Atomic Adsortion Spectrophotometer. The result shows that characteristics of rubber shell activated carbon such as moisture content, ash content, volatile matter have fulfilled National Standard of Indonesia (SNI) except ash content of activated carbon that activated by 20% phosphoric acid. Surface area of activated carbon has fulfilled the standard of commercial adsorbent. The largest adsorption capasity is obtained using Rubber shell activated carbon that activated by 40% phosphoric acid with adsorption percentage 96,67%.